Intermittent hypoxic stimulation promotes efficient expression of Hypoxia-inducible factor-1α and exerts a chondroprotective effect in an animal osteoarthritis model. - Ryota Cha; Shuji Nakagawa; Yuji Arai; Atsuo Inoue; Naoki Okubo; Yuta Fujii; Kenta Kaihara; Kei Nakamura; Tsunao Kishida; Osam Mazda; Kenji Takahashi (PLoS ONE)
Hypoxia-inducible factor-1α plays an important role in the homeostasis of articular cartilage in hypoxic environments. Therefore, modulation of hypoxia-inducible factor-1α by regulating the oxygen environment could be a useful treatment for osteoarthritis. This study aimed to assess the chondroprotective effects of intermittent hypoxia on cultured chondrocytes and an animal model of osteoarthritis. In vitro, human chondrocytes were exposed to 2 h of hypoxic stimulation three times at 1-h intervals, and protein and gene expression of hypoxia-inducible factor-1α, ACAN, and cell viability was measured over time. In vivo, 8-week-old male Wistar rats were injected with monosodium iodoacetate to induce osteoarthritis and then reared in 12% hypoxia for 24 h, followed by 24 h in steady oxygen, repeated alternately for a total of 28 days. A histological analysis was performed on days 8 and 28. In the intermittent hypoxia group, each protein expression increased with each repeated hypoxic stimulation to human chondrocytes; finally, the protein level was significantly higher with intermittent hypoxia than with continuous hypoxic stimulation, cell viability was increased, and gene expression was not significantly increased. In the osteoarthritis animal model, for 8 days, there were stronger hypoxia-inducible factor-1α staining and no significant differences in articular cartilage destruction. Furthermore, for 28 days, there was significantly less articular cartilage destruction in the rat osteoarthritis model with intermittent hypoxia than with steady oxygen rearing. Intermittent hypoxia increased cartilage metabolism by increasing hypoxia-inducible factor-1α proteins in articular chondrocytes, which may be effective in preventing articular cartilage degeneration in a rat osteoarthritis model.